Correlation of pancreatic stone protein PSP with septic shock, SOFA, and APACHE scores: an emerging biomarker for disease severity - Zainulabid, Ummu Afeera; Danapaul, Nabil Anaz Anzani; Kori, Najma; Lau, Chee Lan; Mat Nor, Mohd Basri; Ramly, Nur Fariza; Mansor, Khairul Anam; Cheong, Xiong Khee; Baharuddin, Muhammad Ammar; Meor Jamaludin, Wan Husna Barakah; Ismail, Mohd Helmie; Mohd Junit, Mohd Nadzrul Shah; et al. (Elsevier, 2025)
Pancreatic stone protein (PSP) has emerged as a promising biomarker for disease severity and organ dysfunction. Established markers such as C-reactive protein (CRP), neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), platelet-to-lymphocyte ratio (PLR), and white cell count (WCC) are frequently used in clinical settings to assess systemic inflammation. This study investigates the correlation of PSP and these traditional markers with septic shock, SOFA, and APACHE scores, aiming to enhance understanding of their roles in predicting disease severity and guiding management across varied patient populations.